Oxidative Coupling Reactions for the Estimation of Yohimbine - Begum, Jameelunnisa; Somasekhara Rao, Kaza; Rambabu, C. (Asian Journal of Chemistry, 2010)
Three simple spectrophotometric methods (A–C) for the assay of yohimbine chloride (YHB) in pure state and in formulations have been developed based on the oxidative coupling reaction of YHB, with N,N-dimethylamino p-phenylenediamine (DMPD) in the presence of chloramine-T (CAT) (Method A), 4-aminophenazone (4-AP) in the presence of IO−4 and 3-methyl benzothiazolinone hydrazone (MBTH) in the presence of cerium(IV) [Ce(IV)] (Method C). Regression analysis of Beer-Lambert plots showed good correlation in the concentration ranges 8.0–24.0, 4.0–20.0 and 10.0–50.0 μg/mL for methods A, B and C, respectively. The results of analysis have been validated statistically and by recovery studies.